2023
DOI: 10.1093/hmg/ddac298
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic reduction of GGGGCC repeat RNA levels by hnRNPA3 suppresses neurodegeneration in Drosophila models of C9orf72-linked ALS/FTD

Abstract: The abnormal expansion of GGGGCC hexanucleotide repeats within the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The accumulation of GGGGCC repeat-containing RNAs as RNA foci, and the deposition of dipeptide repeat proteins (DPR) produced from these repeat RNAs by unconventional translation are major pathological hallmarks of C9orf72-linked ALS/FTD (C9-ALS/FTD), and are both thought to play a crucial role in the pathogenesis of these dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Next, we tested whether a reduction in PABPC1 promotes the formation of repeat RNA foci as a disease-associated phenotype of repeat RNA accumulation. 19 , 39 Fluorescence in situ hybridization (FISH) analysis of (G 4 C 2 ) 80 expressing HeLa cells revealed that siRNA-mediated knockdown of PABPC1 increased the number of (G 4 C 2 ) 80 repeat RNA foci positive cells, which is comparable to cells with hnRNPA3 knockdown ( Figures 3 F and 3G). These results suggest that PABPC1 is involved in the degradation pathway of G 4 C 2 repeat RNA as well as hnRNPA3.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Next, we tested whether a reduction in PABPC1 promotes the formation of repeat RNA foci as a disease-associated phenotype of repeat RNA accumulation. 19 , 39 Fluorescence in situ hybridization (FISH) analysis of (G 4 C 2 ) 80 expressing HeLa cells revealed that siRNA-mediated knockdown of PABPC1 increased the number of (G 4 C 2 ) 80 repeat RNA foci positive cells, which is comparable to cells with hnRNPA3 knockdown ( Figures 3 F and 3G). These results suggest that PABPC1 is involved in the degradation pathway of G 4 C 2 repeat RNA as well as hnRNPA3.…”
Section: Resultsmentioning
confidence: 85%
“… 15 , 16 Interestingly, overexpression of wild-type hnRNPA3 reduced poly-GA expression, but RNA-binding ability deficient mutant hnRNPA3 overexpression failed to suppress DPR expression levels in the cellular model or the Drosophila model. 15 , 19 From these observations, we hypothesized that hnRNPA3 that binds to G 4 C 2 repeat RNA may physically interact with RNA degradation factors and facilitate selective RNA degradation in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the hub genes derived from the up-regulated DEGs, no ALS-related literature was found for the EEF1A1 , RPLP0 , EEF2 , CCT2 , RPL12 and RPL15 genes. However, studies related to ALS were identified for the EIF4A1 [ 44 ], HNRNPR [ 45 ], HNRNPA1 [ 45 , 46 ] and PABPC1 genes [ 47 ]. In the case of hub genes obtained from the down-regulated DEGs, only the NDUFA4 gene was associated with ALS-related studies [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that hnRNPA3 preferentially binds to G 4 C 2 and C 4 G 2 repeat RNAs (Mori, Lammich, et al, 2013; Nihei et al, 2020); hnRNPA3 was observed to frequently mislocalize to the cytoplasm, deviating from its physiological nuclear predominant distribution (Boeynaems et al, 2016; Davidson et al, 2017; Fifita et al, 2017; Mori, Lammich, et al, 2013), but hnRNPA3 does not seem to colocalize with RNA foci (Lee et al, 2013). Interestingly, hnRNPA3 suppresses the expression levels of the C9orf72 repeat RNA, through its RNA recognition motifs, and corresponding suppression of DPR expression was observed (Mori et al, 2016; Nihei et al, 2020; Taminato et al, 2023). Moreover, similar to hnRNPA3, expression of IGF2BP1, hnRNPA2B1, and SF3B3, which bind to G 4 C 2 repeat RNA, was found to reduce G 4 C 2 repeat RNA expression in a Drosophila model (Taminato et al, 2023) (Figure 3).…”
Section: Metabolism Of C9 Repeat Rnamentioning
confidence: 99%
“…Interestingly, hnRNPA3 suppresses the expression levels of the C9orf72 repeat RNA, through its RNA recognition motifs, and corresponding suppression of DPR expression was observed (Mori et al, 2016; Nihei et al, 2020; Taminato et al, 2023). Moreover, similar to hnRNPA3, expression of IGF2BP1, hnRNPA2B1, and SF3B3, which bind to G 4 C 2 repeat RNA, was found to reduce G 4 C 2 repeat RNA expression in a Drosophila model (Taminato et al, 2023) (Figure 3). We speculate that these RNA‐binding proteins may exert their effect by promoting the degradation of the repeat RNA.…”
Section: Metabolism Of C9 Repeat Rnamentioning
confidence: 99%